PENGARUH PENGETAHUAN PRODUK DAN PERSEPSI NILAI TERHADAP KEPUTUSAN PEMBELIAN HIJAB RABBANI - Intan Alimuddin; Almansyah Rundu Wonua; Hendrik (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
This research aims to determine: (1) The influence of product knowledge on purchasing decisions for Rabbani hijabs. (2) The influence of perceived value on purchasing decisions for Rabbani hijabs. This research is an Explanatory Research research model with a quantitative approach. Data collection uses observation, documentation and questionnaires. The population in this research is people who have and are currently wearing the Rabbani hijab, namely 120 respondents using a purposive sampling technique, namely a technique for determining certain criteria. Research instrument testing uses validity and reliability tests with SPSS 25.0. The data analysis technique used in this research is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) using the Smart-PLS 4.0 application. Based on the research results, it is known that there is a positive and significant influence between the production variable on purchasing decisions, as well as the value perception variable, there is a positive and significant influence on purchasing decisions.